A time-domain ultrasonic approach for oil film thickness measurement with improved resolution and range. (27th April 2020) - Dou, Pan; Wu, Tonghai; Peng, Zhongxiao
Abstract: The ultrasonic-based method has been proved to be a practical technique for measuring oil film thickness in the enclosed tribo-pair of a supporting bearing and under dynamic conditions. To cope with the large-scale variations of oil film thickness in engineering applications, frequency-domain based models, being adaptive for different measurement ranges, are widely used. As an improvement, the time-domain approach can further expand the effective range, but suffers from decreased resolution in oil thickness measurement. To address these issues, this paper proposes a unified time-domain model for full-range measurement. First, a cluster of standard echoes with definite film thicknesses in a wide range are pre-constructed, and they are matched with measured echoes to find the most suitable oil film thickness. Further, an optimized interpolation is applied to both the constructed and the measured echoes for better resolution. Aiming for the lowest interpolation error, the windowed sinc function was employed optimally. Using a precision calibration rig, the proposed model was compared to the traditional frequency-domain and the time-domain models. The comparison demonstrates that the proposed model has a larger effective measurement range, covering those of all traditional frequency-domain models and with equal accuracies. In addition, the proposed model shows both a wider effective range and a higher resolution than that of the reference time-domain model. This work contributes to the development of on-line continuous measurement of oil film thickness variation at a large scale.